Effect of chronic narcotic use on episode-of-care outcomes following primary anatomic total shoulder arthroplasty. Issue 3 (May 2019) - Mayer, Megan N.; Mulligan, Ryan P.; Villarreal, Arturo D.; Lonergan, Timothy M.; Brolin, Tyler J.; Azar, Frederick M.; Throckmorton, Thomas W.
Abstract : Background: Bundled-care payments for total shoulder arthroplasty (TSA) make early outcomes relevant because they typically are tied to a 90-day episode-of-care. The purpose of this study was to determine the effect of chronic preoperative narcotic use on early postoperative pain relief, narcotic use, length of hospital stay, readmissions, and complications in patients with primary TSA. Methods: Chronic narcotic use was defined as use of narcotic pain medication for at least 3 mo before surgery. Narcotic use was converted to oral morphine equivalents (OME) for in-hospital use, discharge medications, and prescriptions at 2-, 6-, and 12-week visits. Statistical analyses used Fisher's exact test for dichotomous variables and Student's t-test for continuous variables. Differences with P <0.05 were considered statistically significant. Results: Of 152 patients with primary TSA, 27 were chronic preoperative narcotic users and 125 were not. There were no statistically significant differences between groups with regard to age, gender, laterality, or body mass index. At 2 wk postoperatively, there was no significant difference in visual analog scores VAS; however, at 6 and 12 wk, chronic narcotic users had significantly higher VAS and a significantly higher cumulative narcotic requirement. There were no significant differences in length of hospital stay, complications, or readmission rates. Conclusions: Chronic preoperative narcotic use is a risk factor for a more difficult postoperative course after TSA compared to that in narcotic-naïve patients. Chronic opioid users, however, do not necessarily require additional perioperative resources, which is relevant to risk stratification in the emergence of bundled payment programs for TSA. Level of Evidence: Level III, prognostic case-control study.